Regional Disparities in Kidney Transplant Allocation in Brazil: A Retrospective Cohort Study - Salomão Pontes, Daniela Ferreira [UNESP]; Fernandes Ferreira, Gustavo; Segev, Dorry; Massie, Allan B.; Levan, Macey; Barbosa, Abner Mácola Pacheco; da Rocha, Naila Camila; Modelli de Andrade, Luis Gustavo [UNESP] (Wiley, 2024)
Background: Brazil has a large public transplant program, but it remains unclear if the kidney waitlist criteria effectively allocate organs. This study aimed to investigate whether gender, ethnicity, clinical characteristics, and Brazilian regions affect the chance of deceased donor kidney transplant (DDKT). Methods: We conducted a retrospective cohort study using the National Transplant System/Brazil database, which included all patients on the kidney transplant waitlist from January 2012 to December 2022, followed until May 2023. The primary outcome assessed was the chance of DDKT, measured using subdistribution hazard and cause-specific hazard models (subdistribution hazard ratio [sHR]). Results: We analyzed 118 617 waitlisted patients over a 10-year study period. Male patients had an sHR of 1.07 ([95% CI: 1.05–1.10], p < 0.001), indicating a higher chance of DDTK. Patients of mixed race and Yellow/Indigenous ethnicity had lower rates of receiving a transplant compared to Caucasian patients, with sHR of 0.97 (95% CI: 0.95–1) and 0.89 (95% CI: 0.95–1), respectively. Patients from the South region had the highest chance of DDKT, followed by those from the Midwest and Northeast, compared to patients from the Southeast, with sHR of 2.53 (95% CI: 2.47–2.61), 1.21 (95% CI: 1.16–1.27), and 1.10 (95% CI: 1.07–1.13), respectively. The North region had the lowest chance of DDTK, sHR of 0.29 (95% CI: 0.27–0.31). Conclusion: We found that women and racial minorities faced disadvantages in kidney transplantation. Additionally, we observed regional disparities, with the North region having the lowest chance of DDKT and longer times on dialysis before being waitlisted. In contrast, patients in the South regions had a chance of DDKT and shorter times on dialysis before being waitlisted. It is urgent to implement approaches to enhance transplant capacity in the North region and address race and gender disparities in transplantation.
Keywords: disparities; gender bias; healthcare; kidney transplantation; organ transplantation; racial groups; waiting list